Assessing reactive strength measures in jumping and hopping using the Optojump™ system - Healy, R.; Kenny, I. C.; Harrison, A. J. (Journal of Human Kinetics, 2016)
The aim of this study was to assess the concurrent validity of the Optojump™ system (Microgate, Bolzano, Italy) versus a force platform in the estimation of temporal and reactive strength measures. In two separate investigations, twenty physically active males performed double-leg and single-leg drop jumps from a box height of 0.3 m and a 10 s vertical bilateral hopping test. Contact time, flight time and total time (the sum of contact and flight time) were concurrently assessed during single and double-leg drop jumps and during hopping. Jump height, the reactive strength index and the reactive strength ratio were also calculated from contact time and flight time. Despite intraclass correlation coefficients (ICCs) for all variables being close to 1 (ICC > 0.975), a significant overestimation was found in contact time (0.005 ± 0.002 s) and underestimations in flight time (0.005 ± 0.003 s), the reactive strength index (0.04 ± 0.02 m·s-1) and the reactive strength ratio (0.07 ± 0.04). Overestimations in contact time and underestimations in flight time were attributed to the physical design of the Optojump™ system as the transmitter and receiver units were positioned 0.003 m above the floor level. The Optojump™ demonstrated excellent overall temporal validity with no differences found between systems for total time. Coaches are advised to be consistent with the instrumentation used to assess athletes, however, in the case of comparison between reactive strength values collected with the Optojump™ and values collected with a force platform, regression equations are provided.